Pemecahan Masalah Sistem Persamaan Linear Tiga Variabel Ditinjau dari Kecerdasan Emosional Siswa - Savania, Farah Syaifie; Rahaju, Endah Budi (Universitas Negeri Surabaya, 2025)
Problem-solving is an effort to think about solving problems in stages of understanding the problem, devising a plan, carrying out the plan, and looking back. Emotional factors can influence the process. This study aims to describe the problem-solving of a three-variable linear equation system in terms of students' emotional intelligence, so this type of research is descriptive-qualitative. The instruments of this research are an emotional intelligence questionnaire, a problem-solving test, and interview guide. The research subjects were students with low, medium, and high levels of emotional intelligence, each consisting of one student. Data were collected through problem-solving tests and interviews. The research results showed that at the problem-understanding stage, students with low emotional intelligence explained the information in the questions with doubt, while students with medium and high emotional intelligence could explain the information in the questions with confidence. At the devising planning stage, students with low emotional intelligence need direction to devising a plan and are easily influenced by her emotions, while students with high and moderate emotional intelligence can plan solutions confidently. At the carrying out the plan stage, students with low and moderate emotional intelligence have difficulty applying the method and give up easily, while students with high emotional intelligence can apply the completion steps without being influenced by emotions. At the looking back stage, students with low and medium emotional intelligence did not re-examine to check the accuracy of their answers and were resigned, while students with high emotional intelligence diligently re-examined when their answers were wrong. The results of this research provide input for teachers to emphasize the importance of writing information in solving problems and also help strengthen the emotional intelligence of students who have low emotional intelligence.